EFEKTIVITAS PENGGUNAAN SENSOR MQ-7 TERINTEGRASI APLIKASI BLYNK UNTUK MENDETEKSI KEBERADAAN GAS CO DI UDARA - Mugi Lestari; Upik Nurbaiti; Fianti Fianti (Universitas Lambung Mangkurat, 2021)
The development of industry and human living system recently bring effect toward the air quality. Carbon monoxide (CO) which is one of the air pollutant produced by the imperfect ignation which contain carbon of industry, vehicles, and other activities. The existance of carbon monoxide (CO) which is difficult to recognize because of it’s characters which are colourless, cannot be felt or tasteless, cannot be smelt or have no smell, cannot be seen by bare eyes, it means that it needs a tool to help human detect the existance of carbon monoxide. This importance of detector tool of carbon monoxide is because carbon monoxide is quite dangerous for human health if it’s degree is over the limit. There are quite cases of poisoned people who finally died. In this research, the effectiveness test of the use of MQ-7 censor which is integrated with the Blynk application compared with the CO-meter is done. The result shows that MQ-7 is effective to be used in detection and measurement the degree of CO in the air. The integration with Blynk application on the smartphone helps researcher to do the monitoring from everywhere, as long as it is connected to the internet. The price which is more economical also becomes one of the considerations, so CO detector by using MQ-7 censor inegrated with the Blynk application can be done by many groups of society, either industries or individuals.